(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Chitosan is a naturally derived polymer that has been extensively investigated for its use as a biomaterial for local drug delivery and anti-inflammatory activity. Recently, chitosan applications in periodontal tissue healing have gained significant interest. Objectives The present study was undertaken to evaluate the efficacy of chitosan nanoparticle gel when used as an adjunct to scaling and root planing in terms of clinical outcomes and antimicrobial activity. Methods The study was conducted following a split-mouth design in which patients with chronic periodontitis were selected and test and control sites were randomized. Test sites received chitosan nanoparticle gel administration adjunct to scaling and root planning while control sites were subjected to scaling and root planing. Subgingival plaque samples were collected for RT-PCR analysis at baseline and follow-up after 6 weeks. Results It was observed that there was a significant reduction in PI (p-value: 0.002) and PD scores (p-value: 0.001) along with a gain in CAL (p-value: 0.001) in the test group when chitosan nanoparticle gel (1%) was used as an adjunct to SRP. There was no statistically significant difference seen with mean GI scores (p-value: 0.387). Further, chitosan nanoparticle administration significantly reduced counts of P.gingivalis and T.forsythia in the test sites than the control sites. Conclusion Administration of 1% chitosan nanoparticle gel adjunct to scaling and root planning in chronic periodontitis patients resulted in a significant improvement in clinical parameters while exhibiting inhibitory action against the periodontal pathogens P.ginigivalis and T.forsythia. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 177-187